ANALISA PERBANDINGAN EFISIENSI WAKTU DAN BIAYA UDITCH DAN BOX CULVERT UNTUK PENANGANAN SALURAN EXISTING - Rifqi Sahrul Nurhuda; Eko Siswanto; Faiz Muhammad Azhari (LPPM Universitas Abdurrab, 2025)
This study addresses the challenge of drainage construction in narrow, high-traffic locations along Slamet Riyadi Road, Kediri, through a comparative analysis of 266-meter precast U-Ditch and Box Culvert systems. The primary objective is to evaluate the cost and time efficiency of both systems using an integrated approach: (1) technical data collection from CV. Kembar Karya Consultant and PUPR Regulation No. 30/2025, (2) dimensional modeling using AutoCAD, and (3) simulation of the Budget Plan RAB and schedule using Microsoft Excel with S-curves. The results reveal three crucial findings: First, U-Ditch yields significant cost savings of 40% IDR 359,704,257 with a total budget of IDR 547,820,228 compared to Box Culvert's IDR 907,524,485. Second, U-Ditch's unit cost is only IDR 2,109,818/unit – 76% lower than Box Culvert's IDR 3,708,762/unit. Third, although Box Culvert installation commenced three weeks earlier, U-Ditch completed the main installation phase one week faster 4 weeks vs. 5 weeks with 18% higher peak productivity 60-70 units/week vs. 51-52 units/week. These savings enabled the reallocation of IDR 360,000,000 for high-quality sidewalk integration. The study confirms U-Ditch's superiority as the optimal solution for cost-time efficiency in urban infrastructure rehabilitation.